Survey Data and Experimental Choices on Breeding Professionals' Use of Market Intelligence - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
This dataset presents survey data and experimental choices concerning breeding professionals' utilization of market intelligence. Both the survey and the experiment were conducted online through Qualtrics. The survey reached a broad network of plant breeding professionals associated with CGIAR and NARES centers, as well as the private sector. The experiment was distributed to a randomly selected subsample of breeding professionals who had previously completed the survey. The survey gathered information on the application of market intelligence in market segmentation, target product profiling, and decision-making for product advancement or investment cases in breeding pipelines. Additionally, the survey documented respondents' perspectives on diversity and power dynamics within breeding teams. The experiment aimed to understand respondents' shifts in investment preferences based on the type of market intelligence provided and their demand for market intelligence.